Americanism : New Perspectives on the History of an Ideal - McCartin, Joseph Anthony (The University of North Carolina Press, 2008)
The contributors to this volume recognize Americanism in all its complexity--as an ideology, an articulation of the nation's rightful place in the world, a set of traditions, a political language, and a cultural style imbued with political meaning. In response to the pervasive vision of Americanism as a battle cry or a smug assumption, this collection of essays stirs up new questions and debates that challenge us to rethink the model currently being exported, too often by force, to the rest of the world. Crafted by a cast of both rising and renowned intellectuals from three continents, the twelve essays in this volume are divided into two sections. The first group of essays addresses the understanding of Americanism within the United States over the past two centuries, from the early republic to the war in Iraq. The second section provides perspectives from around the world in an effort to make sense of how the national creed and its critics have shaped diplomacy, war, and global culture in the twentieth and twenty-first centuries. Approaching a controversial ideology as both scholars and citizens, many of the essayists call for a revival of the ideals of Americanism in a new progressive politics that can bring together an increasingly polarized and fragmented citizenry.